1997
DOI: 10.3109/02770909709055380
|View full text |Cite
|
Sign up to set email alerts
|

Patient Referrals to a Multispecialty Asthma Clinic

Abstract: A total of 656 patients with asthma have been referred to a multispecialty pediatric asthma clinic for evaluation; 52 (7.9%): mild; 406 (61.9%): moderate; 177 (27%): severe; and 21 (3.2%): incomplete data. No significant differences in demographics or payer source were observed across disease severity levels. Only 25% of the patients with primary care providers were referred by these practitioners. Over 20% of the mild asthmatics were using inhaled bronchodilators regularly. Only 40% and 50% of the moderate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Asthma severity was classified using self-reported clinical characteristics based on the 1998 NHLBI asthma severity of illness classification. 4,23 Access to care and resource utilization measures are shown in Figure 1, panel B. The AC families were more likely to report having access to a physician to call to assist with outpatient management than the ED controls, 98.2% vs 65% (OR = 25.3; 95% CI = 9.0 to 76.9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Asthma severity was classified using self-reported clinical characteristics based on the 1998 NHLBI asthma severity of illness classification. 4,23 Access to care and resource utilization measures are shown in Figure 1, panel B. The AC families were more likely to report having access to a physician to call to assist with outpatient management than the ED controls, 98.2% vs 65% (OR = 25.3; 95% CI = 9.0 to 76.9).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by James et al, only 40% of patients with moderate persistent asthma and 50% of patients with severe persistent asthma were using bronchodilators regularly and correctly. 23 In the same study, only 19% of moderate and 36% of severe persistent asthmatic patients were taking maintenance inhaled corticosteroids. 23 Factors that were significantly associated with inadequate medication therapy included: age <5 years old, Medicaid insurance, and Spanish language.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, more than 75% of the recommendations in an Agency for Health Care Policy and Research-sponsored guideline on the treatment of pressure ulcers were based on only expert opinion. 15 A few studies [16][17][18] have evaluated the use of clinical guidelines by primary care physicians. A recent meta-analysis 16 showed that little evidence existed to support the contention that the use of guidelines by primary care providers actually improved patient care.…”
Section: See Also Page 1089mentioning
confidence: 99%